2020
DOI: 10.36740/wlek202007124
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Students’ Health and Its Improvement in the Process of Physical Education

Abstract: The aim is to investigate the state of health of the students of Ukrainian higher education institutions. Materials and methods: The study of state of health was conducted at Polissia National University and Zhytomyr Ivan Franko State University in 2008-2019. The results of a medical examination of 3737 students of different faculties between the ages of 17 and 22 were examined. Medical examinations were conducted by the doctors of the medical centers of universities. Totally 1208 pupils (male and female) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 15 publications
(15 reference statements)
4
15
0
1
Order By: Relevance
“…The conducted research showed that the current system of physical education at HEI of Ukraine is not effective enough to strengthen the health of students. Our results are confirmed by the conclusions of many scientists [1,4,12] who believe that the traditional form of physical education classes leads to a decrease in students' interest in physical education. Many scientists [7,16,20] argue that one of the most relevant forms of physical education organization is a sports-oriented form of training.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The conducted research showed that the current system of physical education at HEI of Ukraine is not effective enough to strengthen the health of students. Our results are confirmed by the conclusions of many scientists [1,4,12] who believe that the traditional form of physical education classes leads to a decrease in students' interest in physical education. Many scientists [7,16,20] argue that one of the most relevant forms of physical education organization is a sports-oriented form of training.…”
Section: Discussionsupporting
confidence: 88%
“…The system of modern medical higher education is aimed at training a highly qualified specialist who is able to perform significant amounts of work without reducing the quality and intensity and must have a high level of psychomotor qualities that reflects the requirements for physical and mental health, physical fitness and working efficiency of students, future doctors [1,2]. However, the analysis of the scientists' research results [3,4,5] showed a low level of physical fitness of most modern students and a constant increase in the number of people with impaired health both at the beginning and in the process of studying at Ukrainian higher education institutions (HEI).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in life expectancy of the male population in Ukraine and in Western Europe is 12.8 years, and premature mortality, especially among working-age men, is 3-4 times higher than in Europe. More than 70 % of the adult population of Ukraine has low and below average levels of physical health [6,7]. The structure of morbidity is dominated by chronic non-communicable diseases (cardiovascular diseases, malignant neoplasm, mental and endocrine disorders, allergic manifestations), which are characterized by negative dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Physical fitness is an important indicator of the health and physical education of students, which ensures their readiness to perform the physical activities provided by the curriculum at higher education institutions (HEI) [1,2,3]. Physical fitness characterizes the level of physical qualities development, which was achieved in the process of physical education [4,5,6].…”
Section: Introductionmentioning
confidence: 99%